2008
DOI: 10.1038/sj.ki.5002692
|View full text |Cite
|
Sign up to set email alerts
|

Decreased renal ischemia–reperfusion injury by IL-16 inactivation

Abstract: T-cell-mediated renal injury is a major cause of kidney transplant rejection and renal failure; hence, understanding T-cell migration within the kidney is important for preventing renal injury. Interleukin (IL)-16 is a T-cell chemoattractant produced by leukocytes. Here we measured IL-16 expression in the kidney and its role in renal ischemia-reperfusion injury induced by different conditions in several strains of mice. IL-16 was strongly expressed in distal and proximal straight tubules of the kidney. The IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 55 publications
2
23
0
1
Order By: Relevance
“…IL-16 is a T-cell chemoattractant produced by leukocytes. Wang et al reported that IL-16 was a critical factor in the development of inflammation-mediated renal injury and may be a therapeutic target for prevention of ischemia-reperfusion injury of the kidney (Wang et al, 2008). A plethora of studies have also implicated IL-16 in exacerbation of infectious, immune-mediated, and autoimmune inflammatory disorders, including atopic dermatitis, irritable bowel syndrome, systemic lupus erythematosus, neurodegenerative disorders, and viral infections (Glass et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IL-16 is a T-cell chemoattractant produced by leukocytes. Wang et al reported that IL-16 was a critical factor in the development of inflammation-mediated renal injury and may be a therapeutic target for prevention of ischemia-reperfusion injury of the kidney (Wang et al, 2008). A plethora of studies have also implicated IL-16 in exacerbation of infectious, immune-mediated, and autoimmune inflammatory disorders, including atopic dermatitis, irritable bowel syndrome, systemic lupus erythematosus, neurodegenerative disorders, and viral infections (Glass et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of models of acute inflammation have established IL-8 as a key mediator in neutrophil-mediated acute inflammation (31). Wang et al reported that IL-16 was a critical factor in the development of inflammation-mediated renal injury and may be a therapeutic target for prevention of ischemia-reperfusion injury of the kidney (32). Animal studies suggest that CCR3 is a prominent mediator of allergic responses and that antagonizing the receptor will lead to a reduction in airway inflammation (33).…”
Section: Discussionmentioning
confidence: 99%
“…The T cells have been attributed to play a significant role in the pathogenesis of renal IRI [50,51,52]. Studies have shown both direct and indirect blockade of T cells reduced renal functional and structural injury in murine renal IRI models [51,52,53]. In athymic nu/nu mice (T-cell knockout mouse strain) subjected to IRI, not only protection from initial renal injury but also an adoptive T-cell transfer into these mice restored the renal injury [54].…”
Section: Role Of Thymoglobulin In Ischemia-reperfusion Injurymentioning
confidence: 99%